(3NRGfI Gdabgs - (3GdSeQbfOj, CHh GddjK, EeGe GdgOi, fUQ Hf eMeO Hf CMeO Hf EHQGgje, (B373 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bGd CHh GddjK GdSeQbfOj GYde Cf Gdabg Yde MSf hgh CLd ef SGjQ GdYdhe hgh Yde GdOjf hGdTQjYI hbO GSJLeYJ aj gPG GdJCdja ef eSGFd Gdabg hjSei NRGfI Gdabgs
(3BNQgG (B:s
(3hdh bGd dQLd hEMdGd HcQg (B" (3j (B" (3abGd CMQGe jG (B" (3He (B" (3MdGd QGLg cfe cGaQ fcQg hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 27s
(3eYLe GdeDdajf (B4 / 24s
(3cTa GdXfhf (B1 / 703s
(3gOjI GdYGQajf (B2 / 490s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs